Kompetensi Sumber Daya Manusia Sebagai Pemoderasi Kinerja Keuangan Badan Usaha Milik Desa - Sri Ayem; Idris Ramadhan (Jurnal Akuntansi Manado (JAIM), 2024)
This research aims to examine the impact of internal control systems, digital entrepreneurship, and accounting information systems, as well as the moderating effect of human resource competence, on the financial performance of Village-Owned Enterprises. The study employed a survey method, collecting data from 62 BUMDes administrators across Bantul. Data were analyzed using multiple linear regression and moderated regression analysis.The results of the study indicate that digital entrepreneurship and accounting information systems do have an impact on financial performance. Furthermore, the relationship between internal control systems and financial performance, as well as accounting information systems and financial performance, can be strengthened by human resource competence. The findings contribute to helping village administrators understand the importance of digital entrepreneurship and accounting information systems in improving financial performance, while emphasizing the need for developing human resource competencies. This research also provides valuable insights for local governments in designing effective policies and support programs.